The Interaction Between Orthodontics and Periodontal Tissue Remodeling - Abasi , Mina; Goodarzi, Ali; Solhmirzaei, Raheleh; Fazel, Fatemeh; Moharrami, AmirMohammad; Ghasemi, Hamid; Alavi Milani, Haniyeh (Galen Medical Journal, 2025)
Orthodontic tooth movement (OTM) involves a complex cascade of biomechanical and biological events, orchestrated through the interaction of mechanical forces, inflammatory responses, and cellular remodeling within the periodontal ligament and alveolar bone. In adult patients, particularly those with a history of periodontitis, these processes are further complicated by reduced regenerative capacity, chronic inflammation, and altered bone dynamics. This review explores the mechanobiological foundations of OTM, detailing the roles of osteoclasts, osteoblasts, fibroblasts, and endothelial cells, as well as the central regulatory pathways, including RANKL/OPG signaling, cytokine cascades, and matrix metalloproteinase activity. Special attention is given to the clinical implications of orthodontic forces in healthy versus compromised periodontium, emphasizing the importance of force magnitude, direction, and regimen. Interdisciplinary coordination between orthodontists and periodontists is essential for safe and effective treatment planning, particularly when regenerative procedures such as bone grafting, guided tissue regeneration, or the use of biologics like enamel matrix derivative and platelet-rich fibrin are involved. The review also identifies critical knowledge gaps, including uncertainty regarding optimal treatment timing post-periodontal therapy, a lack of long-term and patient-centered outcomes, and the underrepresentation of adult-specific data in clinical research. Emerging technologies in tissue engineering, biomarker analysis, and digital orthodontic planning offer promising avenues for precision-based care. Ultimately, a collaborative, individualized approach that integrates biological insight with clinical expertise is key to achieving both periodontal stability and orthodontic success in periodontally vulnerable patients